Analisis Tata Kelola Sistem Informasi Koperasi Simpan Pinjam Berbasis Framework COBIT 5 - Ni Made Sarminiati; Putri Anugrah Cahya Dewi; Ni Made Estiyanti (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2022)
In its operation, the Kubu Bingin Cooperative Information System often experiences problems related to system access, so that users cannot use the system and must record transactions manually. This causes losses as a result of delays in service to cooperative members. This study aims to analyze the Governance of Information Systems at the SIKOPDIT Savings and Loans Cooperative, using the COBIT 5 Framework. The analysis was conducted to determine the maturity level of governance on a desktop-based system that has been implemented by the Kubu Bingin Cooperative so far. Data collection was carried out by interviews, questionnaires, and documentation studies. The data obtained was analyzed with ISO/ICE 15504 of IT governance, so that the capability level of IT governance can be identified. Based on the results of the analysis, the average capability level in the EDM04, APO01, APO07, BAI09, DSS03, and MEA01 domains is established and the maturity level expected by the Kubu Bingin Cooperative is at level 4 (predictable) so that the results can be used as a reference in process improvement. IT governance in Kubu Bingin Cooperative.Keywords: Savings and Loans Cooperative; Governance; Information Technology; COBIT 5 AbstrakDalam operasinya, Sistem Informasi Koperasi Kubu Bingin sering mengalami permasalahan yang berkaitan dengan akses sistem, sehingga pengguna tidak dapat menggunakan sistem dan harus mencatat transaksi secara manual. Hal tersebut menimbulkan kerugian sebagai akibat tertundanya pelayanan kepada anggota koperasi. Penelitian ini bertujuan menganalisis Tata Kelola Sistem Informasi pada Koperasi Simpan Pinjam SIKOPDIT, dengan menggunakan Framework COBIT 5. Analisis dilakukan untuk mengetahui tingkat kematangan tata Kelola pada sistem berbasis desktop yang sudah diterapkan oleh Koperasi Kubu Bingin selama ini. Pengumpulan data di lakukan dengan wawancara, kuesioner, dan studi dokumentasi. Data yang diperoleh dianalisis dengan ISO/ICE 15504 dari tata kelola TI, sehingga tingkat kapabilitas dari tata kelola TI dapat di ketahui. Berdasarkan hasil Analisa, rata-rata tingkat kapabilitas pada domain EDM04, APO01, APO07, BAI09, DSS03, dan MEA01 adalah established dan tingkat kematangan yang di harapkan oleh Koperasi Kubu Bingin yaitu pada level 4 (predictable) sehingga hasilnya dapat dijadikan acuan dalam peningkatan proses tata kelola TI di Koperasi Kubu Bingin.